Dynamics of the aeolian landform at the coastal geosite of Parangtritis sand dune area, Yogyakarta - Malawani, Mukhamad Ngainul; Mardiatno, Djati; Mutaqin, Bachtiar Wahyu; Suhendro, Indranova; Setiawan, Nicky; Muharram, Fajrun Wahidil; Rhosadi , Iwan (Journal of Degraded and Mining Lands Management, 2024)
In 2014, Kelud, an active volcano in East Java, ejected ashes (hereafter termed KA; Kelud ash) that reportedly reached as far as Central Java and the Special Region of Yogyakarta (DIY). The KA deposits are observable in, among others, the coastal sand dune area in Parangtritis. Due to the active aeolian process, the KA layers can be found at different depths five years after the eruption. Thus, the KA can be used as a marker of the post-2014 aeolian activities at the Parangtritis dune, which was once classified as a degraded land and later recognized as a coastal geosite, ultimately allowing us to calculate the volume and sand transport rate. The research surveys performed at 25 points discovered volcanic ash layers at 1 cm to 26 cm below the surface. At some observed points, the ash deposits were found on the surface and continuously transported. This research observed an area of 60,000 m2 with an average of 8.5 cm thick sand layers lying above the KA layer. Based on the calculation, the total volume of the transported sand at the Parangtritis sand dune from 2014 to 2019 was approximately 5,100 m3. This volume is considerably small owing to various obstacles in the transport zones. Based on the five-year dynamic of the sand dune, this study suggested that restoration needs to be conducted immediately particularly in eliminating vegetation barriers to maintain the sediment balance (erosion-transport-sedimentation) of the coastal sand dune area.